ANALISIS PENYEBAB STUNTING DITINJAU DARI KETAHANAN PANGAN - Hardianti H.P Alam; Cipto Cipto; Desy Dwi Cahyani; Nurmawsti Nurmawsti (Ensiklopedia of Journal, 2026)
Stunting is one indicator of chronic malnutrition caused by insufficient nutrient intake over a long period of time. This condition is not only related to inadequate food intake, but also influenced by the low quality of food consumed. The purpose of this study was to analyze the causes of stunting in terms of food security. A cross-sectional study design was used in this study. The research was conducted in the working area of the Cempaka Inpatient Health Center. The research was conducted in April 2024. The research population consisted of mothers who had toddlers in the working area of the Cempaka Inpatient Health Center. The sample consisted of 58 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between food security (p value: 0.038) and the incidence of stunting. This study recommends improving food security by ensuring the adequacy of family food needs through coping strategies and paying attention to household expenditures by prioritizing the nutritional needs of toddlers. Keywords: Toddlers, Food Security, Stunting